Pengaruh Metode Drill and Practice terhadap Keterampilan Membaca Pemahaman Siswa Kelas V SDI Assalam Pasir Randu - Lestari, Nurul; Dahlan, M. Azdi; Mawardi, Mawardi (Lembaga Yasin AlSys, 2021)
This study aims to obtain information on reading comprehension skills of students who are taught by drill and practice methods and those taught conventionally, as well as obtain information on differences in reading comprehension skills of students taught by drill and practice methods and those taught conventionally. This type of research itself is a quasi-experimental type of quantitative research, in this study the sampling technique was carried out using a saturated sampling technique, namely the overall sampling technique. In this study, the sample used was all fifth grade students at SDI Assalam Pasir Randu using a test. Based on calculations using the t-test at the time of the pretest, the value of tcount> ttable (-3.0 > 2.021), while at the time of the protest was obtained the value of tcount> ttable (3.1 > 2.021) with a significant level of = 0.05. The average value of the experimental class using the drill and practice method is 78.2 and the average control class using the conventional method is 69.58. So the use of the drill and practice method is better than the conventional method.